OLYMPIAD MATERIAL DEVELOPMENT FOR IMPROVING OF TEACHER PROFESSIONALISM MGMP SMP REGENCY OF AGAM WEST REGION - Arnellis Arnellis; Elita Zusti Jamaan; Minora Longgom Nasution; Defri Ahmad (Fakultas MIPA Universitas Negeri Padang, 2018)
Based on observations and interviews with several mathematics teachers of Agam west region, the teacher's lack of knowledge about non-routine materials and problems in mathematical olympiad. Teachers rarely attend the olympic training so that teachers do not know much about non-routine questions, techniques to solve the problem. Based on these observations and the facts there is and so the importance of making the strengthening of mathematics material for teachers. The purpose of this article is to provide the strengthening of mathematics olympiad material so that teachers can improve their professional development, especially in making and solving the olympic problem in teachers of SMP MGMP west Agam District. Based on the evaluation it can be seen that generally the participants of community service in general have sufficiently understood the material in designing the problem and how to solve the existing problems in the Olympics in order to improve the quality of OSN participants from west Agam District. This success is shown by the teacher is able to design and make problems and solve problems related to mathematics olympiad.